2015
DOI: 10.3201/eid2112.140659
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of IntermediateLeptospiraspp. DNA in Febrile Humans from Urban and Rural Ecuador

Abstract: Intermediate clusters may cause disease in areas where dengue and malaria are present, so differential diagnosis is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 27 publications
(42 reference statements)
1
49
0
1
Order By: Relevance
“…In addition to pathogenic species, other members of the Leptospira genus referred to as intermediates or saprophytes cause mild to no disease in humans (Chiriboga et al, 2015;Ko, Goarant, & Picardeau, 2009). Genomic comparisons between these species groups have revealed a number of important differences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pathogenic species, other members of the Leptospira genus referred to as intermediates or saprophytes cause mild to no disease in humans (Chiriboga et al, 2015;Ko, Goarant, & Picardeau, 2009). Genomic comparisons between these species groups have revealed a number of important differences.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some of the species from the "intermediate" or pathogenic Leptospira spp. group II clade have been increasingly found in febrile cases in humans (Levett et al, 2006;Chiriboga et al, 2015;Tsuboi et al, 2017;Puche et al, 2018) and causing disease in different animal species (Zakeri et al, 2010;Romero-Vivas et al, 2013). Hence, these reports highlight the relevance of studying this group of Leptospira spp.…”
Section: Introductionmentioning
confidence: 90%
“…Although this species group has been detected in environmental soil and water samples from the Southeast Asia ( 4 6 ), human cases involving returned travelers have not been well-documented previously ( 1 , 7 – 10 ). To our knowledge, only 2 cases of L. licerasiae isolation from a human host have been reported; such isolations were first reported in Peru in 2008 ( 7 ) (Table), although many serum samples from febrile patients in the Peruvian Amazon have reacted with an L. licerasiae isolate.…”
mentioning
confidence: 99%
“…Leptospira species are classified into 3 groups on the basis of 16S rRNA gene sequences: pathogenic, intermediate, and saprophytic groups. Although Leptospira species from the pathogenic group are considered to be the main cause of leptospirosis, Chiriboga et al reported that most cases of leptospirosis in Ecuador were caused by intermediate species ( 1 ). We describe a case of leptospirosis caused by L. licerasiae , an intermediate species, in a traveler returning to Japan from Brazil.…”
mentioning
confidence: 99%